Biological activities of fructooligosaccharide (FOS)-containing Coix lachryma-jobi Linn. extract - Manosroi J. (2014)
Fructooligosaccharide (FOS), a prebiotic was extracted from the grain of Coix lachryma-jobi Linn. (Job's tears) by hot water extraction at 60 C for 1 h. The resulting dried powder extract was assayed for FOS content of 1-kestose (GF2), nystose (GF3) and 1-β-D-fructofuranosylnystose (GF4) using HPLC equipped with RI detector. Total FOS content of the extract was 24.98 ± 7.48% (g/100 g crude extract). The biological activity including antioxidant and cytotoxicity of the FOS-containing extract was determined. The antioxidant activity by DPPH free radical scavenging of FOS-containing extract was comparable to vitamin C (0.97 fold of vitamin C) with a slight lipid peroxidation inhibition activity. The extract exhibited no cytotoxic effect on normal human skin fibroblast. These results have confirmed not only the source of FOS from Job's tears extract but also its potential application as antioxidant in food or cosmetic products. © 2011 Association of Food Scientists & Technologists (India).